1995
DOI: 10.1128/aem.61.1.92-97.1995
|View full text |Cite
|
Sign up to set email alerts
|

In situ inactivation of animal viruses and a coliphage in nonaerated liquid and semiliquid animal wastes

Abstract: The persistence of five animal viruses, representing picorna-, rota-, parvo-, adeno-, and herpesviruses, and the coliphage f2 was determined in the field by exposing the viruses to different animal wastes and by adopting an established filter sandwich technique. This technique allows us to copy the natural state of viruses in the environment, where adsorption onto or incorporation into suspended solids may prolong virus survival. Using filter sandwiches either equipped with porous (15 nm in diameter) or porele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…The kinetic trends observed in this study were generally consistent with studies using real matrices (19,26,30,(34)(35)(36)58), although some works reported contradictory results (25,27,32,37). This may be due to the high complexity of real matrices compared to the well-controlled solutions used in this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The kinetic trends observed in this study were generally consistent with studies using real matrices (19,26,30,(34)(35)(36)58), although some works reported contradictory results (25,27,32,37). This may be due to the high complexity of real matrices compared to the well-controlled solutions used in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Instead, the virucidal activity of NH 3(aq) likely involves modification or damage of the virus components (i.e., protein, envelope, or nucleic acid). However, while numerous studies have investigated the fate of viruses in complex matrices containing NH 3(aq) (8,17,19,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), the virucidal mechanism of action of NH 3(aq) has received little scrutiny to date (38,39).…”
mentioning
confidence: 99%
“…There is good evidence that inactivation of viruses in the environment is less effective if they are absorbed onto or embedded within suspended solid matter that is not dried out. Viruses like HAV, NoV and HEV can resist complete inactivation in the environment for a very long time (Pesaro et al ., ).…”
Section: Environmental Matrices Containing Human Pathogenic Virusesmentioning
confidence: 97%
“…Knowledge is incomplete about the viral attributes and environmental factors that contribute to viral inactivation (40). The stability of different viruses varied, apparently depending on whether the virus particle was adsorbed to or embedded within suspended solids (40). Other factors that affect viral survival include pH, temperature, and the presence of bacteria that can inactivate viruses (10).…”
Section: Virusesmentioning
confidence: 99%